Do butterfly communities benefit from woodland restoration in rural environments? A landscape perspective from south‐eastern Australia. Issue 1 (29th July 2021) - Ouin, Annie; Holland, Greg J.; Tessier, Marc; Clarke, Rohan H.; Bennett, Andrew F.
Abstract : Restoration of degraded ecosystems is a global issue, particularly in rural regions where excessive loss of natural vegetation has occurred. We investigated, at both landscape and patch scales, the benefits to butterfly communities of restoration by revegetation (planting trees and shrubs), typical of many rural landscapes in south‐eastern Australia. We surveyed eight pairs of landscapes (200 ha each) dominated either by remnant or restored woody vegetation, along a gradient of wooded cover. In total, 1, 683 individuals of 11 butterfly species were recorded by transect counts, with the fauna dominated by four generalist species. At the landscape scale, there were similar patterns of occurrence of butterflies in remnant and restored landscapes: species richness was not related to the gradient in wooded cover, but overall abundance of butterflies increased with wooded cover. At the patch scale there was a similar richness of butterflies in revegetation and remnants (greater than in pasture), with abundance greater in remnants. Individual species showed distinctive responses to patch types (i.e. remnants, revegetation, scattered trees, pasture). In all patch types, the ground layer was dominated by exotic plants and most observations (78%) of butterflies taking nectar were from exotics. Revegetation in farmland created new wooded habitat, at least for common butterfly species, despite the study being undertaken during severe drought. Benefits of revegetation will be enhanced by actions at both the landscape scale (extent, connectivity of habitat), and patch scale (habitat quality) through promoting native ground‐layer species favored for adult foraging and as larval host plants.